If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3(3 + -2x) = 3(-2 + 2x) + -3x + -7 4x + (3 * 3 + -2x * 3) = 3(-2 + 2x) + -3x + -7 4x + (9 + -6x) = 3(-2 + 2x) + -3x + -7 Reorder the terms: 9 + 4x + -6x = 3(-2 + 2x) + -3x + -7 Combine like terms: 4x + -6x = -2x 9 + -2x = 3(-2 + 2x) + -3x + -7 9 + -2x = (-2 * 3 + 2x * 3) + -3x + -7 9 + -2x = (-6 + 6x) + -3x + -7 Reorder the terms: 9 + -2x = -6 + -7 + 6x + -3x Combine like terms: -6 + -7 = -13 9 + -2x = -13 + 6x + -3x Combine like terms: 6x + -3x = 3x 9 + -2x = -13 + 3x Solving 9 + -2x = -13 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 9 + -2x + -3x = -13 + 3x + -3x Combine like terms: -2x + -3x = -5x 9 + -5x = -13 + 3x + -3x Combine like terms: 3x + -3x = 0 9 + -5x = -13 + 0 9 + -5x = -13 Add '-9' to each side of the equation. 9 + -9 + -5x = -13 + -9 Combine like terms: 9 + -9 = 0 0 + -5x = -13 + -9 -5x = -13 + -9 Combine like terms: -13 + -9 = -22 -5x = -22 Divide each side by '-5'. x = 4.4 Simplifying x = 4.4
| 2x+4.7=7.5 | | r^2=-40+13r | | 3x-17=-32 | | (2/5)(1/5) | | 2b+4=-17.2 | | 8=4(7x+3) | | x-47-4x=5-7x-19+3x | | 2x-12x^2+32=0 | | 3r^2-122r+500=0 | | 0.5x+2=10 | | x*x+3x+4=5 | | P(x)=2x^4-3x^3-14 | | 58.3=10-8m | | x=1.333333333+-1.666666667y | | 117+45=180 | | 3(s)-5=27 | | .75n=-5.25 | | 19.19+n=26.19 | | -3(-3z+7)= | | -10-5x=8 | | 5.25n=-36.75 | | x-31-4x=5-7x-38+3x | | xty=-5 | | 2x^4+2x=37x+2 | | 4(x-5)2=36 | | 4(x-5)squared=36 | | 3xty=-21 | | 2x/3-1/6=5x/6-2/3 | | 3(-1+7x)=102 | | -9+7x-4x=0 | | X-2y=2/3 | | 5x+5+75+75=180 |